Combination of Berberine and NVP-BEZ235 inhibits metastasis of triple-negative breast cancer MDA-MB-231 cell line - Demirci, Zuleyha; Yesilay, Gamze; Nalbantoglu, Barbaros; Bolat, Zeynep Busra (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
Triple Negative Breast Cancer (TNBC), responsible for 20 % of breast cancers cases, is the most lethal and aggressive type. Its resistance to hormonal therapy and frequent development of chemotherapy resistance render conventional treatments inadequate for TNBC. The phosphatidylinositol 3-kinase (PI3K)/AKT/mTOR pathway, commonly activated in breast cancer, is critical in tumor growth and metastasis. Inhibitors for this pathway have shown to have therapeutic potential and their combinations has led to their active investigation in preclinical and clinical studies for TNBC treatment. Berberine is an isoquinoline alkaloid that shows low toxicity and anticancer activities and inhibits epithelial-mesenchymal transition (EMT) and autophagy in cancer cells. This study investigates the synergistic effect of the dual PI3K/mTOR inhibitor, NVP-BEZ235, with Berberine on the TNBC MDA-MB-231 cell line. Cell viability assays demonstrated dose- and time-dependent cytotoxic effects and a combination of 10 mu M berberine and 0.25 mu M NVP-BEZ235 was selected as the effective dose at 48 h. Health mammary epithelial MCF-10 A cell line showed less toxicity compared to MDA-MB-231 cells in the combination treatment. MDA-MB-231 cells showed a significant reduction in migratory ability and suppression of cell growth and colony formation ability when treated with combination of Berberine and NVP-BEZ235. Treatment with Berberine and NVP-BEZ235 combination led to an accumulation of cell population at G0/G1 phase of MDA-MB231 cells. MDA-MB-231 cells treated with Berberine and NVP-BEZ235 showed a significant reduction in ncadherin and slug gene expression, while e-cadherin gene expression levels increased significantly. Ligand tracer results show that the combination of Berberine and NVP-BEZ235 reflects the stabilizing effect of NVP-BEZ235 on Berberine binding kinetics in MDA-MB-231 cells. These findings suggest a synergistic effect of NVP-BEZ235 and Berberine combination inhibiting metastasis of MDA-MB-231 cell line, demonstrating a potential therapy for TNBC.
Keywords: Triple negative breast cancer; Berberine; PI3K/AKT/mTOR pathway; Migration; Metastasis; DOWN-REGULATION; PHASE-I; APOPTOSIS; TARGET; TRANSITIONS; DOXORUBICIN; PATHWAY; CYCLE; EMT; Biochemistry & Molecular Biology; Biophysics